Mycorrhizal compatibility and symbiotic reproduction of Gavilea australis, an endangered terrestrial orchid from south Patagonia - Fracchia, Sebastian (2014)
Gavilea australis is a terrestrial orchid endemic from insular south Argentina and Chile. Meeting aspects of mycorrhizal fungi identity and compatibility in this orchid species is essential for propagation and conservation purposes. These knowledge represent also a first approach to elucidate the mycorrhizal specificity of this species. In order to evaluate both the mycorrhizal compatibility and the symbiotic seed germination of G. australis, we isolated and identified its root endophytic fungal strains as well as those from two sympatric species: Gavilea lutea and Codonorchis lessonii. In addition, we tested two other strains isolated from allopatric terrestrial orchid species from central Argentina. All fungal strains formed coilings and pelotons inside protocorms and promot- ed, at varying degrees, seed germination, and protocorm de- velopment until seedlings had two to three leaves. These results suggest a low mycorrhizal specificity of G. australis and contribute to a better knowledge of the biology of this orchid aswell as of other sympatric Patagonian orchid species, all of them currently under serious risk of extinction.